2018
DOI: 10.1161/circep.118.006242
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNA-21 Correlates With Left Atrial Low-Voltage Areas and Is Associated With Procedure Outcome in Patients Undergoing Atrial Fibrillation Ablation

Abstract: Circulating miR-21 correlates with left atrial LVAs and is associated with procedure outcome in patients with persistent AF undergoing ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 36 publications
3
38
0
Order By: Relevance
“…Participants with AF had lower plasma levels of miR-21 compared to controls, and miR-21 expression increased 1 month after catheter ablation 7 . The circulating miR-21 level is also associated with AF ablation results in patients with persistent AF undergoing ablation (and this level correlates with left atrial low voltage areas) 8 . Other studies have shown higher levels of miRNAs 125a, 10b, 601, 30a-3p, and 199b in patients with 12-month AF recurrences after catheter ablation than in patients without AF recurrences 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Participants with AF had lower plasma levels of miR-21 compared to controls, and miR-21 expression increased 1 month after catheter ablation 7 . The circulating miR-21 level is also associated with AF ablation results in patients with persistent AF undergoing ablation (and this level correlates with left atrial low voltage areas) 8 . Other studies have shown higher levels of miRNAs 125a, 10b, 601, 30a-3p, and 199b in patients with 12-month AF recurrences after catheter ablation than in patients without AF recurrences 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that miRs function as important regulators that participates in DM-induced atrial brosis 35 . The role of miR-21 in the pathogenesis of atrial brosis has been illuminated, and increased miR-21 expression was correlated positively with atrial brosis or brotic gene expression [20][21][22] signaling pathway by decrease CADM1 expression 58 . In our mice diabetic model, we also found that miR-21 KO manifested a decreased atrial brosis as well as brotic gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Their main function is to regulate post-transcriptional regulation of target genes expression by binding to the 3' untranslated region (3'-UTR) 19 . MicroRNA-21 (miR-21) has been shown to be associated with atrial brosis in previous studies [20][21][22] . But most of its mechanisms focused on the damage of cardiomyocytes and the activation of broblasts.…”
Section: Introductionmentioning
confidence: 99%
“…This process correlates with collagen, connective tissue growth factor, lysyl oxidase and Rac-1-GTPase contents in left atrial tissue [40]. Moreover, miR-21 regulates the signal transducer and activator of transcription 3 (STAT3) pathway, through which it induces inflammation-associated atrial fibrosis [41]. STAT3 is an important regulator of cell proliferation via downstream signaling molecule of Cell adhesion molecule 1 (CADM1).…”
Section: Association Between Microrna and Structural Remodeling Of Lamentioning
confidence: 99%
“…A significant correlation between the relationship of miR-21 serum concentrations and 1-year outcome after catheter ablation in patients with persistent AF has been described. It could be assumed that circulating miR-21 can be useful for stratifying patients and planning the procedure (e.g., performing a pulmonary vein isolation only in patients with very low miR-21 serum concentrations or planning extensive substrate modification in patients with high miR-21 levels) [41].…”
Section: Association Between Microrna and Structural Remodeling Of Lamentioning
confidence: 99%